2023
DOI: 10.7150/ijbs.80775
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy alleviates cisplatin-induced renal tubular epithelial cell ferroptosis through ROS/HO-1/GPX4 axis

Abstract: Cisplatin is widely recommended in combination for the treatment of tumors, thus inevitably increasing the incidence of cisplatin-induced acute kidney injury. Mitophagy is a type of mitochondrial quality control mechanism that degrades damaged mitochondria and maintains cellular homeostasis. Ferroptosis, a new modality of programmed cell death, is characterized by iron-dependent phospholipid peroxidation and oxidative membrane damage. However, the role of mitophagy in ferroptosis in kidney disease is unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 68 publications
3
25
0
Order By: Relevance
“…At the beginning of this experiment, we treated KGN cells with gradient concentrations of cisplatin to establish injured models. Cisplatin has been authenticated to induce the occurrence of ferroptosis in some cancer cells [ 42 ] and renal tubular epithelial cells [ 43 , 44 ]. We first proved cisplatin can induce ferroptosis in KGN cells in a dose-dependent manner by detecting the protein expression levels of ferroptosis-related molecules such as GPX4, Nrf2, FTH1 and SLC7A11.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of this experiment, we treated KGN cells with gradient concentrations of cisplatin to establish injured models. Cisplatin has been authenticated to induce the occurrence of ferroptosis in some cancer cells [ 42 ] and renal tubular epithelial cells [ 43 , 44 ]. We first proved cisplatin can induce ferroptosis in KGN cells in a dose-dependent manner by detecting the protein expression levels of ferroptosis-related molecules such as GPX4, Nrf2, FTH1 and SLC7A11.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of ER-phagy is slightly different from mitophagy in AKI. Mitophagy is irritability elevated in AKI, which indicates the protective role for eliminating mitochondrion after injury [ 13 15 , 36 ]. Nevertheless, in the present study, we show ER-phagy is reduced in contrast to IRI, cisplatin, and folic acid-induced AKI, and meanwhile, ER stress and apoptosis are aggravated, which suggests that IRI or drugs might directly work on ER and reduce ER-phagy, resulting downstream accumulation of ER stress and renal tubular epithelial cell death in AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin mice were treated as outlined in our previous work [ 15 ]. Mice were administered cisplatin (Jiangsu Hansoh, H20040813, 20 mg/kg body weight) via intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%
“…Its protective role is attributed to the production of biliverdin and its toxic effects are due to excessive accumulation of Fe 2+ . However, a growing number of studies have shown that hyperactivation of HMOX1 increases cytotoxicity [22][23][24].…”
Section: Introductionmentioning
confidence: 99%